Patterns of eating associated with the chronic diseases in Al-Ahsa, Saudi Arabia - Al Sayegh, Hassan Ali; Al Qurini, Abdulaziz Adel; Khan, Abdul Sattar; Ibrahim, Sayed (International Journal Of Community Medicine And Public Health, 2017)
Background: There is increase in the limitation of daily activity of people with chronic diseases. This may be due to multiple factors one of them is the nature of the lifestyle for instance, patterns of eating that the person is following. It is important to sum the dietary behaviors in specific population to see how much is it associated with chronic diseases. Specially, obesity, cardiovascular diseases, diabetes and sickle cell disease which are endemic diseases in Al-Ahsa. Moreover, no studies have been conducted in this area before. It is known that there is increased obesity, cardiovascular and diabetes prevalence in Al-Ahsa. The study aims to see the association between chronic diseases and eating patterns. Methods: Cross sectional study, self-reported questionnaire distributed to the population under supervision of the data collectors in Al-Ahsa, during the summer of 2017. Results: The most prevalent chronic disease is obesity. Then comes hypertension and G6PD. Obesity showed most association with other chronic diseases. Also, eating frozen canned food show associations with obesity, hypertension, G6PD and diabetes. Conclusions: We concluded that there are certain eating behaviors influences some chronic diseases; there should be a focus on these behaviors to prevent the occurrence of these chronic diseases, especially metabolic diseases. Obesity is the primary concern which may facilitate the developing of hypertension, asthma, diabetes, high cholesterol, G6PD, hypothyroidism, hyperthyroidism, diabetes, sickle cell disease and cardiovascular events.